What Work Is : poems - Levine, Philip (Alfred A. Knopf)
Philip Levine (Detroit, 1928) ha obtenido dos veces los premios Pulitzer, National Book Award y National Book Critics Circle Awards y una vez el Leonore Marshall Award y el Ruth Lilly Award. Algunas de sus obras son: The Return; The Simple Truth; Wat Work Is; Unselected Poems; The Bread of Time: Toward an Autobiography.